Urgensi Rekonseptualisasi Undang-Undang Penataan Ruang Terhadap Transfer Of Development Rights - De Ekberg, Jasmine Rahmafiola; Koeswahyono, Imam; Adianto, Daru (RechtJiva, 2026)
There is an element of incompleteness of law in Law Number 26 of 2007 concerning Spatial Planning because there is no concept of Transfer of Development Rights (TDR), especially in the aspect of the scheme between parcels (land plots) above land rights, such as Ownership Rights and Building Use Rights (HGB), and currently the legal practice of Transfer of Development Rights (TDR) has been carried out, but Transfer of Development Rights (TDR) has no legal basis. This study aims to determine the urgency in reconceptualizing Law Number 26 of 2007 concerning Spatial Planning related to Transfer of Development Rights (TDR) between parcels (land plots) above land rights, especially Ownership Rights and Building Use Rights (HGB) as an effort to control spatial planning; and to determine the limits of regulations on Transfer of Development Rights (TDR) between parcels (land plots) above land rights, especially Ownership Rights and Building Use Rights (HGB) in Law Number 26 of 2007 concerning Spatial Planning. This study uses a normative legal method using a legislative approach and a conceptual approach. The results of the study indicate that there is an urgency to reconceptualize Law Number 26 of 2007 concerning Spatial Planning, namely so that Transfer of Development Rights (TDR) has a legal basis, Transfer of Development Rights (TDR) is one of the instruments in controlling the use of space, Transfer of Development Rights (TDR) is one form of incentive, in order to provide legal certainty in conducting Transfer of Development Rights (TDR)  transactions, as well as the essence of justice in Transfer of Development Rights (TDR) for both parties conducting Transfer of Development Rights (TDR). Not all concepts need to be regulated, to whom the rights are attached (the area to its owner or area manager), given once or periodically.